Good Corporate Governance Practices in Family Business: A Case Study in Indonesia - Wardhana, Daniel Yudistya (Petra International Journal of Business Studies, 2018)
Good corporate governance (GCG) practices have been broadly acknowledged in both industry and government these days. In general, good execution and practice of good corporate governance indicate thehealth of corporations. The awareness of good corporate governance practice developed among familybusiness regardless the size of the business. Thus, this research aims to explore the general perception offamily business towards the good corporate governance practices and the importance of good corporategovernance in their business. The focus of this study is family business in Yogyakarta Province, Indonesia.This research uses descriptive and quantitative model. Every data that was obtained from the respondents willbe described in detail and explained with quantitative model to analysis the implementation of good corporategovernance in SMEs. The results from 60 family businesses show that mostly the SMEs understand thatcompany financial and non-financial report should be reported on regular basis (mean= 2.83) they alsodiscloses the internal salary system to the employee (mean= 2.68) it might be due to the directcommunication by the owner or management to the employees. SMEs agree that detailed job description isnecessary (mean= 2.97) as well as standard operational procedure document (mean= 2.67). Also, most ofSMEs agree that a regular payment period is important (mean= 3.58) and reporting the tax on time(mean=3.27). SMEs agree that the owners or family members should be independent in recruiting employees(mean=2.55) and deciding company strategies (mean=2.43) and SMEs perception of fairness showed thatfamily member have limited opportunity to work at the company (mean=3.30).